Carbon, Nitrogen, and Phosphorus Stoichiometry and Plant Growth Strategy as Related to Land-Use in Hangzhou Bay Coastal Wetland, China - Xiong, Jing; Shao, Xuexin; Yuan, Haijing; Liu, Enjun; Wu, Ming (Frontiers in Plant Science, 2022)
Ecological stoichiometry can not only instruct soil nutrient stocks and availability, but also indicated plant growth strategy and adaptability to environmental changes or stress. This study was carried out to examine the plant–soil Carbon (C), Nitrogen (N), and Phosphorus (P) stoichiometry distributions and patterns in three tidal wetlands [mudflat (MF), native Phragmites australis-dominated community wetland (NW), invasive Spartina alterniflora-dominated community wetland (IW)], and one reclaimed P. australis-dominated community wetland (RW) in Hangzhou Bay coastal wetland. The results showed that land-uses have more effect on C and N contents, and C:N and N:P ratios in plant than in soil, P content and C:P ratios more affected by plant organ and soil depth. Compared to land-use, both plant organ and soil depth have stronger effects on C, N, and P stoichiometry. Among tidal wetlands, plant N content and C:P, N:P ratios were significantly higher in NW than in IW. In contrast, plant C, N, and P contents and C:P and N:P ratios were significantly lower in RW, and plant C:N was higher. Soil C, N, and P stocks were similar between tidal wetlands, and were significant higher than those of RW, indicating that reclamation were not beneficial to soil nutrient storage. In the NW, soil N availability was relatively high, and P availability was relatively low; and leaf N:P was 15.33, which means vegetation was co-limited by N and P nutrients. In addition, plants in the NW mainly adopted a conservative growth strategy, with a significantly low aboveground biomass of 1469.35 g·m2. In the RW, soil N availability was relatively low, P availability was relatively high, and leaf N:P was 3, which means vegetation was limited by N nutrient. In addition, plants in the RW mainly adopted a rapid growth strategy, with a significantly high aboveground biomass of 3261.70 g·m2. In the IW, soil N availability was relatively low, soil P availability was relatively high, and leaf N:P was 5.13, which means vegetation was limited by N nutrient. The growth strategy and aboveground biomass (2293.67 g·m2) of the IW were between those of the NW and RW. Our results provide a reference for nutrient management and evaluating the impacts of land-use types on coastal wetland ecosystems.